Strategy for the development of Dermaji Village Tourism: Building Competitiveness in Rural Tourism in the Post-Pandemic Era - Hariyadi, Bagus Reza; Afif, Fuadi; Herliana, Monika; Firmansyah, Dian Bayu (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
This research aims to identify the tourism potential and formulate competitive rural tourism development strategies in Dermaji Village, Lumbir District, Banyumas Regency, Central Java. The study employs a qualitative descriptive approach using an exploratory case study. Primary data were obtained through in-depth field observations and interviews with key informants, while secondary data were sourced from literature reviews and documentation. The research utilized the analysis of 11 tourism components, modified from various experts, CHSE analysis, government work programs, market preferences, and SWOT analysis, including SWOT Matrix. The findings reveal significant potential and 15 main strategies for developing Dermaji Village into a competitive rural tourism destination. The village has already undertaken initiatives such as collaborating with Perum Perhutani and local community efforts to create unique rural tourism destinations. Active and adaptive strategies are required to develop Dermaji Village into a competitive rural tourism destination with unique offerings in Banyumas Regency, considering both micro and macro perspectives.